PENERAPAN METODE PROFILE MATCHING UNTUK MENENTUKAN KELAYAKAN PEMBERIAN PINJAMAN PADA BANK PERKREDITAN RAKYAT - Veti Apriana (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The determination of the feasibility of granting loans (credit) is very important for the company, many factors need to be considered to make decisions on granting pinajaman (credit) to the credit applicant. It needs a proper assessment attribute determination to avoid mistakes in making decisions that may result in losses. Application of profile matching method used to solve problems that provide credit to an applicant perangkingan best of criteria - criteria that have been mapped with the aim to assist and facilitate the decision maker in providing alternatives to lending to credit applicants. Rate and calculation of the value GAP by home ownership status, status of business, business conditions, the main income, extra income, the ability of monthly installments, credit guarantees, personality. The final step of the method of profile matching the form of rankings shows that the higher the ranking produced, the greater the chances of being accepted for a loan (credit) presented by the Bank. The results showed that the profile matching method can be implemented in a decision support system for assessing the feasibility of granting loans based on the assessment criteria. Keywords : Feasibility credit, Decision Support System